español - PAREDES, LUIS; CHICAIZA, JOHANA (Revista Ecos de la Academia, 2021)
This research arises from the need to implement new pedagogical models in the teaching-learning process of a second language. For this reason, the general objective of this research is to analyze the incidence of the Flipped Classroom Model in the grammatical development of the English language in the students of the First (BGU) of the National Experimental Co-ed High School "Amazonas" in Quito, Ecuador. The focus of the present investigation is qualitative-quantitative, including a non-experimental design, within a descriptive level. The modality of the research is socio-educational with a documentary and field research because the information of the variables is collected through other sources. Additionally, the techniques and instruments for data collection are an interview-open questions guide aimed at teachers, and, on the other hand, an observation is applied to the students. According to the results obtained from the analysis and interpretation of the instruments, it is concluded that the Flipped Classroom model contributes significantly to the grammatical development of the English language. In this sense, a course on technological tools based on the Flipped Classroom model is proposed.KEY WORDS: PEDAGOGICAL MODELS, TEACHING-LEARNING PROCESS, FLIPPED  CLASSROOM MODEL, GRAMMATICAL DEVELOPMENT, MEANINGFUL LEARNING